Visual relations children find easy and difficult to process in figural analogies - Stevenson, Claire E.; Alberto, Rosa A.; van den Boom, Max A.; de Boeck, Paul A. L. (Frontiers in Psychology, 2014)
Analogical reasoning, the ability to learn about novel phenomena by relating it to structurally similar knowledge, develops with great variability in children. Furthermore, the development of analogical reasoning coincides with greater working memory efficiency and increasing knowledge of the objects and rules present in analogy problems. In figural matrices, a classical form of analogical reasoning assessment, some categories, such as color, appear easier for children to encode and infer than others, such as orientation. Yet, few studies have structurally examined differences in the difficulty of rule-types across different age-groups. This cross-sectional study of figural analogical reasoning examined which underlying rules in figural analogies were easier or more difficult for children to correctly process. School children (N=1422, M=7.0 years, SD=21 months, range 4.5-12.5 years) were assessed in analogical reasoning using classical figural matrices and memory measures. The transformations the children had to induce and apply concerned the categories: animal, color, orientation, position, quantity and size. The role of age and memory span on the children’s ability to correctly process each type of transformation was examined using explanatory item response theory models. The results showed that with increasing age and/or greater memory span all transformations were processed more accurately. The “what” transformations animal, color, quantity and size were easiest, whereas the “where” transformations orientation and position were most difficult. However, animal, orientation and position became relatively easier with age and increased memory efficiency. The implications are discussed in terms of the development of visual processing in object recognition versus position and motion encoding, the ventral (“what”) and dorsal (“where”) pathways respectively.